Understanding the difficulties of leadership in the context of social entrepreneurship - Oliveira, Zaila Maria (2023)
Female leadership is a new perspective on leadership, as they seek to bring their intrinsic characteristics to the organizational environment. This research aims to verify the difficulties of female leadership, based on the theoretical assumptions that women face in the context of social entrepreneurship. The research is descriptive with a qualitative approach and field research strategy. The data was collected through interviews with representatives of two Brazilian companies based in the state of Ceará. The results reveal that the discrimination faced by women when they are in strategic positions is a recurring fact in the job market, even more so as they are part of a patriarchal society, particularly in Brazil. It is concluded that women still find themselves in an unfavorable environment, which is unaware of their potential, as well as the ability to overcome already exhausted business and organizational models.